Possible application of gold thin films formed from surfactant free gold nano-particle dispersed in aqueous solutions to surface-enhanced Raman scattering spectroscopy. (13th June 2019) - Matsuda, Naoki; Okabe, Hirotaka; Nagamura, Toshihiko; Uehara, Masato
Abstract: Detailed procedure to form gold (Au) thin films from surfactant free Au nano-particle dispersed aqueous solution prepared by solution plasma processing was investigated for surface-enhanced Raman scattering (SERS) spectroscopy measurement. The averaged diameter, thickness, and the weight of each Au thin film in our experimental conditions from 40 mL of 1% Au dispersed aqueous solution, were evaluated to be around 2.4 mm, 4.6 μm and 0.4 mg, respectively. SERS spectra of dye molecule (crystal violet: CV) adsorbed on Au thin film and silver (Ag) substrate were successfully measured upon excitation at 532 nm of solid type laser and 632.8 nm of He-Ne laser, respectively. These SERS spectra of CV adsorbed both on Au and Ag surfaces were coincided with each other, and the intensity from Au surface was unexpectedly much stronger as compared to those from Ag surface. The possible application of Au thin film for SERS platform on solid/liquid interfaces was demonstrated by observation of SERS spectra from p -nitrothiophenol (PNTP) adsorbed on Au thin film/aqueous solution interface.